2020
DOI: 10.1242/dev.177956
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the pattern of the vertebrate limb

Abstract: The vertebrate limb continues to serve as an influential model of growth, morphogenesis and pattern formation. With this Review, we aim to give an up-to-date picture of how a population of undifferentiated cells develops into the complex pattern of the limb. Focussing largely on mouse and chick studies, we concentrate on the positioning of the limbs, the formation of the limb bud, the establishment of the principal limb axes, the specification of pattern, the integration of pattern formation with growth and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 145 publications
(172 reference statements)
0
68
0
1
Order By: Relevance
“…Similarly, for gracile capuchins (Cebus)-characterised by long slender limbs and a slighter body plan (59, 77)-we recovered various enriched annotated terms related to limb and skeletal system development, including several homeobox transcription factors of the Hox (5 of 21 analysed) and Shox (1 of 2 analysed) families that play fundamental roles in embryonic pattern formation, axis control, and are required for normal limb development (78). Many other genes in these terms are also associated with various skeletal dysmorphologies and congenital limb defects in humans.…”
Section: Body Size and Morphologymentioning
confidence: 99%
“…Similarly, for gracile capuchins (Cebus)-characterised by long slender limbs and a slighter body plan (59, 77)-we recovered various enriched annotated terms related to limb and skeletal system development, including several homeobox transcription factors of the Hox (5 of 21 analysed) and Shox (1 of 2 analysed) families that play fundamental roles in embryonic pattern formation, axis control, and are required for normal limb development (78). Many other genes in these terms are also associated with various skeletal dysmorphologies and congenital limb defects in humans.…”
Section: Body Size and Morphologymentioning
confidence: 99%
“…The FGF10/FGF8 feedback loop is maintained until approximately embryonic day 5.5, or stage 28 in chicken, beyond which it is no longer is able to support proliferation of the underlying mesenchyme 61 . However, during these stages of development, additional signaling centers are established which drive the growth and patterning of the limb and have been comprehensively studied and reviewed 4,11,66‐69 . The resulting embryonic limb comprises three components, the stylopod, zeugopod, and autopod, which, in the mammalian forelimb, form the humerus, radius/ulna, and wrist/phalanges, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although we know much about how the limb is patterned, we know little about how this process is timed between differently sized species. The avian wing provides an excellent system to understand this problem, as we possess in-depth knowledge of the underlying developmental patterning mechanisms that rely on the integration of extrinsic signalling and autonomous timing processes (1) . Thus, the embryonic development of the chick wing involves a switch from proximal signalling from the body wall (humerus/stylopod specification) to an autonomous timing mechanism operating in mesoderm cells at the distal tip of the outgrowing bud (digit/autopod specification) (2)(3)(4)(5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro approaches have revealed that the rate of protein degradation in mouse cells is approximately twice as fast as is found in human cells, and that this correlates with the tempo of somitogenesis and motor neuron differentiation (3,4) . The avian wing provides an excellent in vivo system to understand species developmental timing, as we possess in-depth knowledge of the underlying mechanisms that pattern the proximo-distal axis (humerus to digits), and which rely on the integration of extrinsic signalling and autonomous timing processes (5) . Thus, the specification of the chick wing skeletal pattern involves a switch from proximal signalling from the body wall (humerus/stylopod specification) to an autonomous timing mechanism operating in mesoderm cells at the distal tip of the outgrowing bud (digit/autopod specification) (6)(7)(8)(9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%